Association of Diabetes with Coronary Collateral Formation in Patients with Ischaemic Heart Disease - Karim, Md Fazlul; Hossain, Md Tofazzal; Shahabuddin, Mir Muhammad Shoyeb; Chowdhury, Sanjib (Cardiovascular Journal, 2020)
Background: Although myocardial ischemia is known to be significantly related to the development of coronary collateral vessels (CCVs), there is considerable variation between patients with ischemic heart disease in the presence of collateral development. The nature of this variability is not well known. Likewise, it remains unclear whether diabetes mellitus (DM) has any effect on CCVs. The aim of this study was to evaluate the effect of DM on CCVs. Methods: A total of 100 patients who had a stenosis of >95% in any major coronary artery in angiograms were included in the study. Of these patients, 30 patients constitute the diabetic group. Remaining 70 patients were non-diabetic. For case-control matching, 30 non-diabetic patients (mean age, 52.03± 8.69 years) were selected randomly and were included in the control group. The CCVs were graded according to the Rentrop scoring system, and the collateral score was calculated by summing the Rentrop numbers of every patient. Results: There was no statistical difference between patients with and without DM in clinical baseline characteristics. The mean number of diseased vessels in the DM group (2.10±0.76) was higher than that in the nondiabetic group (1.63± 0.72 P.017). The mean collateral score was (1.13± 0.86) in the DM group and (1.97± 1.61) in the control group. After confounding variables were controlled for, the collateral score in the diabetic group was significantly different from that in the nondiabetic group (p=0.015). Conclusions: Our findings suggest that CCV development is poorer in patients with DM than in patients without DM. Thus, we can speculate that DM is an important factor affecting CCV development. Cardiovasc. j. 2020; 12(2): 89-95